2014
DOI: 10.2754/avb201483030233
|View full text |Cite
|
Sign up to set email alerts
|

Histological characteristics of the musculus longissimus lumborum et thoracis muscle fibres in pigs in relation to selected RYR1, MYOG, MYOD1 and MYF6 genotypes

Abstract: Histochemical and biochemical muscle fibre properties are the factors that influence the quantitative and qualitative characteristics of pork meat. The aim of the study was to assess the influence of genetic effects of selected genetic markers MyoD genes and RYR1 on the achieved indicators of muscle fibres in the musculus longissimus lumborum et thoracis (MLLT). The study included a total number of 216 hybrid pigs with the mean slaughter weight of 123 kg. Gene polymorphism was determined by the PCR-RFLP method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Te pass et al (2004 revealed that the level of MYF4 gene mRNA expression is localized mainly in red muscles in animals at slaughter and is associated with muscle fibre type. Gerześ et al (2010) and Stupka et al (2014) reported significant effect of MYF4 polymorphism on the number of muscle fibres per area unit in pigs. Some authors also showed that the MYF4 gene had also a tendency to regulate backfat thickness (Civaňova and Knoll, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Te pass et al (2004 revealed that the level of MYF4 gene mRNA expression is localized mainly in red muscles in animals at slaughter and is associated with muscle fibre type. Gerześ et al (2010) and Stupka et al (2014) reported significant effect of MYF4 polymorphism on the number of muscle fibres per area unit in pigs. Some authors also showed that the MYF4 gene had also a tendency to regulate backfat thickness (Civaňova and Knoll, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the expectations resulting from previously published studies (Verner et al, 2007;Civaňova and Knoll, 2007;Stupka et al, 2012) all of the MYF4 genotypes showed only non-significant (P<0.05) impact on selected production traits. The associations of MYOD genes family with pork quality has been previously investigated in various pig populations by several studies (Soumillion et al, 1997;Kapelañski et al, 2005;Cinar et al, 2012;Stupka et al, 2014). The MyoD genes were tested as candidate genes with an expected, significant effect principally on the muscle deposition (Kłosowska et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation